Konsep Peeragogy Untuk Pembelajaran PAI Yang Bermakna Di Sekolah Dasar - Nuri, R Nurhayati; Hasmiati, Hasmiati; Ningsih, Diarti Andra; Qadrianti, Laeli; Islamiah, Nurul; Kadir, Muhammad; Ahmad, Nur Akmal; Oktavianty, Nur (Universitas Islam Ahmad dahlan, 2024)
Peeragogy is a learning concept that is based on the thoughts that each person has. Students participate in study groups with their own way or understanding and knowledge so that the learning process occurs easier and better. The presence of learning partners in learning is equipped with different information regulations between students so that they can exchange information which broadens each student's understanding and relationships. Strategy is a set of interdependent parts to achieve desired goals and objectives. A learning strategy can also be interpreted as a model of learning activities which can be selected and used contextually according to the characteristics of the students, the conditions of the learning environment and the surrounding environment that support it, as well as the specific learning objectives that are formulated. Peeragogy is an educational strategy that introduces students to education to focus on learning to work and be creative. The aim of this research is to investigate and describe the application of peeragogy strategies for meaningful PAI learning